A Platinum Molecular Complex Immobilised on the Surface of Graphene as Active Catalyst in Alkyne Hydrosilylation. Issue 45 (3rd June 2020) - Mollar‐Cuni, Andres; Borja, Pilar; Martin, Santiago; Guisado‐Barrios, Gregorio; Mata, Jose A.
Abstract : A platinum complex bearing a N‐heterocyclic carbene (NHC) ligand functionalised with a pyrene‐tag is immobilised onto the surface of reduced graphene oxide (rGO). The hybrid material composed of an organometallic complex and a graphene derivative is ready available in a single‐step process under mild reaction conditions. This methodology preserves the inherent properties of the active catalytic centre and the support. The platinum hybrid material is an efficient catalyst in hydrosilylation of alkynes and can be recycled and reused without significant loss of activity due to its high stability. Interestingly, the catalytic activity of the platinum complex is not affected by diffusion problems after immobilisation. The influence of graphene in hydrosilylation of alkynes is discussed in terms of activity and selectivity. Abstract : Development of a hybrid material composed by a well‐defined platinum complex and graphene is described. The immobilization is achieved in a single step by functionalization with a pyrene tag and thanks to the formation of π‐stacking interactions. This methodology paves the way for direct access of solid catalysts that allow catalyst recycling and improve catalyst efficiency.